Chlorhexidine Preserves Dentin Bond in vitro - Carrilho, M. R. O. (2007)
Loss of hybrid layer integrity compromises resin-dentin bond stability. Matrix metalloproteinases (MMPs) may be partially responsible for hybrid layer degradation. Since chlorhexidine inhibits MMPs, we hypothesized that chlorhexidine would decelerate the loss of resin-dentin bonds. Class I preparations in extracted third molars were sectioned into two halves. One half was customarily restored (etch-and-rinse adhesive/resin composite), and the other was treated with 2% chlorhexidine after being acid-etched before restoration. Specimens were stored in artificial saliva with/without protease inhibitors. Microtensile bond strengths and failure mode distribution under SEM were analyzed immediately after specimens' preparation and 6 months later. With chlorhexidine, significantly better preservation of bond strength was observed after 6 months; protease inhibitors in the storage medium had no effect. Failure analysis showed significantly less failure in the hybrid layer with chlorhexidine, compared with controls after 6 months. In conclusion, this in vitro study suggests that chlorhexidine might be useful for the preservation of dentin bond strength.